Neuromuscular Electrical Stimulation Under Deep Sedation Reduces the Incidence of ICU-Acquired Weakness in Critically Ill Patients With COVID-19 With Acute Respiratory Distress Syndrome - Miyagishima, Saori; Akatsuka, Masayuki; Tatsumi, Hiroomi; Takahashi, Kanako; Bunya, Naofumi; Sawamoto, Keigo; Narimatsu, Eichi; Masuda, Yoshiki (Curēus (Palo Alto, CA), 2024)
The COVID-19 pandemic has led to an unprecedented increase in cases of acute respiratory distress syndrome (ARDS). In such cases, deep sedation using sedatives and muscle relaxants is commonly used to prevent patient self-inflicted lung injury during the early phase. However, such sedation limits the ability to perform early rehabilitation, leading to ICU-acquired muscle weakness (ICU-AW) and a worse prognosis. This study aimed to clarify the preventive effect of neuromuscular electrical stimulation (NMES) during deep sedation on ICU-AW and physical function at discharge in critically ill patients with COVID-19 with ARDS. A retrospective, single-center study was conducted on patients admitted to the ICU or advanced critical care center with severe COVID-19 with ARDS between March 1, 2020, and March 31, 2022. Patients who were managed with the Richmond Agitation-Sedation Scale between -4 and -5 for at least three days were included. Patients in the NMES group received NMES within two days of deep sedation, whereas those in the non-NMES group did not. The primary endpoint was the incidence of ICU-AW at discharge from the ICU, and the secondary endpoints included physical activity levels, skeletal muscle mass index, time to active mobilization, and Barthel index (BI) at discharge. Statistical analyses included Pearson's chi-squared test, Fisher's exact test, and multiple logistic and linear regression analyses. Of the 129 patients, 68 (54 males and 14 females) were included after applying the exclusion criteria, with 38 in the NMES group and 30 in the non-NMES group. The incidence of ICU-AW was significantly lower in the NMES group (28.95% vs. 56.67%, p = 0.0211). NMES implementation (OR: 0.20, p = 0.03), ventilator weaning (OR: 0.10, p = 0.01), and duration of deep sedation (OR: 0.81, p < 0.01) were significant predictors of ICU-AW. Higher ICU Mobility Scale scores and shorter time to active mobilization were associated with a higher BI at discharge. Early rehabilitation using NMES during deep sedation may prevent ICU-AW in critically ill patients with COVID-19 with ARDS. NMES is associated with a reduced risk of ICU-AW and improved functional independence at discharge. This procedure can be safely performed in sedated patients and may help prevent ICU-AW, supporting early mobilization strategies in ARDS rehabilitation.